Konsep Keadilan Allah SWT Menurut Al-Qadi' Abd Al-Jabbar - Ibrahim, Mohd Radhi (Jurnal Usuluddin, 2001)
This article is an attempt to illustrate the concept of Justice of God according to al-Qadi 'Abd al-Jabbar.